2007
DOI: 10.1002/ijc.22805
|View full text |Cite
|
Sign up to set email alerts
|

Fat and meat intake and prostate cancer risk: The multiethnic cohort study

Abstract: Dietary fat and meat as potential risk factors for prostate cancer have been the focus of many epidemiologic investigations, and findings from recent studies in particular have been inconsistent. Therefore, we examined the association between these exposures and prostate cancer risk in the Multiethnic Cohort Study. The analyses included 82,483 men in Hawaii and Los Angeles aged 45, who completed a detailed quantitative food frequency questionnaire in [1993][1994][1995][1996]. During the follow-up period of 8 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
132
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(144 citation statements)
references
References 45 publications
11
132
0
1
Order By: Relevance
“…8 -11 However, this is still a matter of controversy because more recent studies have failed to confirm these observations and actually suggest no relationship between dietary fat intake and risk of developing prostate cancer. 12,34,35 Because of the long natural progression of prostate cancer along with the inherent difficulties in performing dietary interventions in human trials, mouse models are commonly used to examine various dietary interventions. Xenograft mouse models of cancer are generally created by a subcutaneous injection of human cancer cell lines into immunodeficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…8 -11 However, this is still a matter of controversy because more recent studies have failed to confirm these observations and actually suggest no relationship between dietary fat intake and risk of developing prostate cancer. 12,34,35 Because of the long natural progression of prostate cancer along with the inherent difficulties in performing dietary interventions in human trials, mouse models are commonly used to examine various dietary interventions. Xenograft mouse models of cancer are generally created by a subcutaneous injection of human cancer cell lines into immunodeficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, 3 case-control studies [Bidoli et al, 2005;Hedelin et al, 2007;Liu et al, 2007], and 3 cohort studies [Park et al, 2007;Neuhouser et al, 2007;Wallström et al, 2007] have reported no association with total fat ( table 2 A, B). Thus, the conclusion does not require modi fication.…”
Section: Total Fatmentioning
confidence: 98%
“…In this subgroup analysis, a significant positive association between the combination of EPA and DHA intake and total prostate cancer incidence (relative risk (RR) = 1.135; 95 % CI = 1.008-1.278; p = 0.036; I 2 = 25 %, p = 0.249) was found by combining the results of only two studies (Wallstrom et al, 2007;Chavarro et al, 2008). The analysis was repeated by adding two cohorts (Schuurman et al, 1999;Park et al, 2007) which had only addressed and analysed intakes of EPA and DHA separately in relation to prostate cancer risk. This analysis revealed no significant association between DHA and EPA intake and prostate cancer risk and no significant heterogeneity among studies.…”
Section: Prospective Cohort Studies On Epa and Dha Intakes And Risk Omentioning
confidence: 99%